220k views
0 votes
Square Root

Factor the perfect-square trinomial on the left side of the equation. Apply the square root property of equality. (looking for the answer to the second part)

Square Root Factor the perfect-square trinomial on the left side of the equation. Apply-example-1
User Chelsie
by
5.2k points

2 Answers

6 votes

Answer:

1. Perfect square trinomial on left sides is
(x+(1)/(4))^2=(4)/(9).

2. The equation after applying the square root property of equality is
x+(1)/(4)=\pm (2)/(3).

Explanation:

The given equation is


x^2+(1)/(2)x+(1)/(16)=(4)/(9)

It can be written as


x^2+(1)/(2)x+((1)/(4))^2=(4)/(9)

Factor the perfect-square trinomial on the left side of the equation.


x^2+2((1)/(4))x+((1)/(4))^2=(4)/(9)


(x+(1)/(4))^2=(4)/(9)
[\because (a+b)^2=a^2+2ab+b^2]

Therefore the required equation is


(x+(1)/(4))^2=(4)/(9)

Taking square root both the sides.


\sqrt{(x+(1)/(4))^2}=\pm\sqrt{(4)/(9)}


x+(1)/(4)=\pm (2)/(3)

Therefore the equation after applying the square root property of equality is
x+(1)/(4)=\pm (2)/(3).

User Alan Bowen
by
5.9k points
6 votes

Answer:

1).
(x+(1)/(4))^(2)=(4)/(9)

2).
x+(1)/(4)=\pm (2)/(3)

Explanation:

Here the given equation is
x^(2)+(1)/(2)x+(1)/(16)=(4)/(9)

We have to factor the perfect square trinomial on the left side of the equation

So left side of the equation is
x^(2)+(1)/(2)x+(1)/(16)

=
x^(2)+2* (1)/(4)x+((1)/(4))^(2)


=(x+(1)/(4))^(2) since [(a+b)²= a²+b²+2ab]

Therefore the factorial form of the equation will be


(x+(1)/(4))^(2)=(4)/(9)

Now we have to solve the equation by applying square root property


\sqrt{(x+(1)/(4))^(2)}=\sqrt{(4)/(9)}


x+(1)/(4)=\pm (2)/(3)

User Yanchi
by
5.0k points